Content and distribution of oxides of the generation depending on the granulometric composition of the donal sediments of the rivers of Ukraine - Alekhina, Tatiana M. (Journal of the Belarusian State University. Ecology, 2018)
The article presents the results of studies of the content and distribution of iron oxides in the bottom sediments of the Dnieper, Yuzhny Bug, Ingulets and Ingul rivers. The dependence of the content and distribution of iron oxides on the granulometric composition of river sediments is analyzed. The iron oxide content has high positive correlation coefficients with the pelitic precipitation fraction for all the studied rivers, with the exception of Ingulz. It is shown that changes in the Fe2O3 / FeO ratio make it possible to reveal the presence of reducing conditions in bottom sediments.
Keywords: bottom sediments of rivers; iron oxides; granulometric composition of sediments